PENGEMBANGAN VIDEO PEMBELAJARAN ANAK-ANAK BERBASIS ANIMAKER UNTUK MENINGKATKAN MINAT DAN EFEKTIVITAS PEMBELAJARAN - Carli Apriansyah Hutagalung; Wida Nofiasari (Jurnal Abdimas Bina Bangsa, 2023)
Indonesian children's interest in learning decreases from year to year, many factors influence it, especially in this study in the Rawa Kucing Final Disposal Area (TPA) area, the low interest in children's learning and the lack of effectiveness of conventional learning and some stop because economic factor. This service tries to examine the level of enthusiasm, interest and effectiveness of children's learning through the use of Animaker animated characters in learning videos at the Indonesian Light Learning House TPA Rawa Kucing Kedaung Wetan. This study uses the Field Work Practice (PKL) approach. The results of this study indicate that Animaker-based learning videos are effective in increasing children's interest and knowledge transfer and making a positive contribution to the development of interesting learning approaches for children. Animaker-based learning videos can be an effective tool for increasing children's learning interest, strengthening conceptual understanding, and creating fun learning experiences